Pelatihan dokumen Digital Land Document Application Training Towards a Digital Village at the Kujung Village Government : Pelatihan Aplikasi Dokumen Pertanahan Menuju Desa Digital Pada Pemerintahan Desa Kujung - Nurma*, Nur Mahmudah; Ningrum, Ifa Khoiria; Yuwita, Pelangi Eka (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Digital-based data management is essential for village development, particularly in managing digital land documents. These documents significantly enhance the efficiency of data management, making it easier for residents to search, input, and update information. The primary objective of our community service initiative is to equip Kujung Village government employees with the necessary knowledge and skills for effective digital land document management. Our implementation approach involves three stages: execution, evaluation, and monitoring to ensure program sustainability. On September 26, 2024, at Kujung Village Hall, 15 village officials, 4 BPD members, and 6 LKMD members participated enthusiastically in the program. The results indicated a strong consensus among participants regarding the proposed indicators, and a notable increase in their understanding. Consequently, village officials showed a greater inclination to utilize digital applications for data management over traditional manual methods. This initiative has also led to improved services that are faster, more transparent, and accountable